A EAD como instrumento de inclusão social: uma análise crítica sobre o processo de institucionalização da EAD no curso de pedagogia do centro de educação da UFPB - Sousa, Grazielli Martins Pereira de (2018)
This dissertation was developed on ODL as an instrument of social inclusion: a critical analysis of the process of institutionalization of ODL in the course of Pedagogy of the Education Center of the UFPB. The general objective was to analyze the process of institutionalization of the EaD in the Pedagogy course of the Education Center of the UFPB in the perspective of social inclusion. The research was developed in three distinct but complementary moments, in the first one a bibliographical research was done that used as reference theoretical studies carried out by Brandão (2008), Belloni (2008), Boaventura (2005), Bogdan (1994), Castells ), Dourado (2011), Freitas (2016), Levy (1999), among others; in the second moment a documentary research was carried out in the archives of the Pedagogy course to highlight the Curriculum Guidelines for the Pedagogy course CNE / CP 01/2006, the creation of the UFPB distance pedagogy course Resolution CONSEPE 23/2007 and the Pedagogical Project of the course established by specific resolution CONSEPE / UFPB 12/2013. Finally the field research, the study presented a qualitative approach, with methodological characteristics of case study, which as instruments of data collection were adopted: the process of interviews applied to coordinators and teachers and also a questionnaire was applied to tutors, with open questions. It was verified that the possibilities of social inclusion through EaD brought an expansion of public higher education courses in this modality in order to promote "inclusion" of social groups that were historically excluded as people from different regions of the interior who did not have access to teaching superior in the face-to-face modality, the elderly, blacks, Indians and the poor. However, what has been observed is the expansion of a private market destined for a public that has been excluded and a new way to profit on a large scale and unbridled and quality is not on the same level.